أثر أسلوب الحوار الإيجابي على التوافق الزواجي لدى الأساتذة الجامعيين - ديدي، نسرين, مقيرحي، صفاء (جامعة الوادي university of Eloued, 2020)
ملخص البحث - هدفت الدراسة الحالية لمعرفة أسلوب الحوار وأثره على التوافق الزواجي لدى أساتذة قسم العلوم الاجتماعية والإنسانية بجامعة الوادي. وبما أن دراستنا تبحث عن أثر الحوار الإيجابي على التوافق الزواجي لدى عينة الدراسة، لذا اخترنا المنهج السببي المقارن الأنسب لمثل هذه الدراسة. حيث إستخدمنا استبيانين : 1-الحوار 2-التوافق الزواجي لمعرفة أسلوب الحوار وأثره على التوافق الزواجي لدى أفراد العينة، حيث تمثلت أفراد العينة من 90 زوجا وزوجة حسب متغيرات :العمر، التخصص، مدة الزواج، السكن، عدد الأبناء، الجنس ونصت الفرضيات الدراسة على : -يوجد أثر إيجابي بين الحوار والمعاملة الانسانية -يوجد أثر إيجابي بين الحوار تحمل المسؤولية -يوجد أثر إيجابي بين الحوار والخلافات الزوجية -يوجد أثر إيجابي بين الحوار والتوافق الجنسي -يوجد أثر إيجابي بين الحوار والنضج الانفعالي والعاطفي -يوجد أثر إيجابي بين الحوار والرضا والسعادة الزوجية ولخصت تحت فرضية عامة وهي: -يوجد أثر إيجابي بين الحوار والتوافق الزواجي لدى الأساتذة الجامعيين. -لم نتمكن من استكمال وتحقيق من الفرضيات بسبب ما تمر به البلاد من جائحة وباء كورونا نسأل الله العافية. Summary: The current study aimed to find out the method of dialogue and its impact on marital compatibility among professors of the Department of Social Sciences and Humanities at El-Wadi University. Since our study is looking for the effect of positive dialogue on marital compatibility among the study sample, we chose the causal-comparative approach best suited to such a study. Where we used two questionnaires: 1- Dialogue 2- Marital compatibility to find out the method of dialogue and its effect on marital compatibility among the sample members, as the sample members consisted of 90 husbands and wives according to variables: age, specialization, length of marriage, housing, number of children, sex. : There is a positive effect between dialogue and humane treatment There is a positive effect between dialogue and taking responsibility There is a positive effect between dialogue and marital disputes There is a positive effect between dialogue and sexual compatibility There is a positive effect between dialogue and emotional and emotional maturity There is a positive effect between dialogue and marital satisfaction and happiness It is summarized under a general premise, namely: There is a positive effect between dialogue and marital compatibility among university professors. - We were not able to complete and verify the assumptions due to what the country is going through in terms of the Corona pandemic. WeaskGod for good health.
دراسة وصفية بكلية العلوم الاجتماعية والإنسانية جامعة الوادي
مذكرة ماستر في علوم التربية تخصص إرشاد وتوجيه
Keywords: التوافق الزواجي، الحوار; Compatibilité conjugale, dialogue; Marital compatibility, dialogue